2000
DOI: 10.1046/j.1365-2141.2000.02244.x
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative study of peripheral blood stem cell contamination in diffuse large‐cell non‐Hodgkin's lymphoma: one‐half of patients significantly mobilize malignant cells

Abstract: Autologous transplantation using peripheral blood stem cells (PBSCs) collected after chemotherapy, followed by growth factor administration (ASCT), is increasingly used in the treatment of non‐Hodgkin's lymphoma (NHL). However, quantitative data regarding contaminating malignant cells in the harvests are still scarce. We prospectively investigated 37 diffuse large‐cell lymphomas (DLCLs) in complete remission (CR) that were treated according to multicentric protocols at our centre. DNA was extracted from the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 22 publications
0
22
1
Order By: Relevance
“…When possible (ALL), a monthly follow-up of residual disease was carried out using a methodology previously described. 16 Results…”
Section: Patients and Donorsmentioning
confidence: 99%
“…When possible (ALL), a monthly follow-up of residual disease was carried out using a methodology previously described. 16 Results…”
Section: Patients and Donorsmentioning
confidence: 99%
“…In addition, BM and PBSC harvests from patients with B-cell malignancies are recognized to frequently contain malignant cells. [18][19][20][21] Studies employing genetic markers have implicated these graft contaminants as a potential source of relapse post-auto-SCT. 22,23 Strategies to decrease FL relapse post-auto-SCT must reduce or eliminate both of these sources of lymphoma cells.…”
Section: Introductionmentioning
confidence: 99%
“…In this setting, residual disease and tumor contamination of transfused stem cells are the main causes for relapse of DLBCL. The presence of minimal residual disease (MRD) is a known poor prognostic indicator in DLBCL patients who undergo transplantation (16).…”
Section: Discussionmentioning
confidence: 99%
“…The use of rituximab for the in vivo purging of hematopoetic stem cell products has yielded encouraging results in disease eradication (up to 79% of MRD rendered undetectable after in vivo purging with rituximab), resulting in five-year OS and PFS of up to 78% (16)(17)(18)(19)). An ongoing prospective study in patients with relapsed follicular lymphoma showed that the use of rituximab for in vivo graft purging and maintenance therapy following auto-STC resulted in undetectable MRD in a high proportion of patients (12).…”
Section: Discussionmentioning
confidence: 99%